A Review of Crop Protection Methods against the Twospotted Spider Mite—Tetranychus urticae Koch (Acari: Tetranychidae)—With Special Reference to Alternative Methods - Magdalena Jakubowska; Renata Dobosz; Daniel Zawada; Jolanta Kowalska (Agriculture, 2022)
Tetranychus urticae is one of the most important pests of many species of economically important crops, cultivated both under cover and in open ground. Feeding T. urticae reduces the size and quality of the yield. Nowadays, in connection with the popularization of organic farming and the green order policy, non-chemical methods that provide an effective reduction in the harmfulness of this spider mite are sought. The aim of the study is to present the current state of knowledge on methods of reducing the undesirable effects of T. urticae feeding. The paper discusses the main directions of searching for biopesticides against T. urticae and provides a list of natural components on which commercially available products are based. The aspect of using the natural properties of plants, micro- and macro-organisms is presented. The paper also deals with the issue of the spread of spider mites in connection with the observed climate changes.